Investigation of the use of Web-centric collaborative product development techniques and methods: The case of software industry - Hwang, Lihsin (University of Ottawa (Canada), 2003)
This research investigated the use of web-centric collaborative techniques and methods for the software industry new product development (NPD) process. After carefully reviewing previous literature, a questionnaire was designed targeting individuals who currently work on or previously participated in the software new product development (NPD) process for the past six months. The survey was launched through the third-party web researching company, InsightExpress, where 200 completed surveys were collected. As the observation from the results of this research indicates, the web-based level of collaborative tools does increase the level of integration between different departments in the NPD process. However, the impact of web-based collaborative tools on either overall performance or performance elements (technical success, financial success, budgetary, time-to market or schedule) is not evident. Moreover, the level of adapting web-based collaborative tools in the software industry is still not as popular as it was anticipated to be.
Keywords: Engineering, System Science.; Computer Science.